Challenges for sustainable agriculture: Using participatory tools to study cocoa and livestock production systems in Caquetá, Colombia - Buitrago Rueda, Juliana; Álvarez Rámirez, Javier (2023)
Participatory rural appraisal (PRA) is a technique for qualitative participatory research that has its origins in the participatory action-research, and which facilitates the dialogue between academic actors and communities, to identify the problems, challenges, and possibilities for rural development. During the PRA workshops implemented during 2023 in the municipalities of Montañita and Belén de Los Andaquíes in the department of Caquetá, Colombia, in the Low-Emissions Food Systems Initiative, the reflections of participants revolved around key themes: from household well-being – which includes the ability to grow crops to ensure food security and obtain income – to gaining access and knowledge to implement sustainable production practices through technical advice. To increase this potential, the participants identified a need for crop diversification, promotion of biodiversity, public policies that support farmers and investment in systems that respond to current environmental conditions. The difficulties identified in achieving sustainable food systems included lack of knowledge, limited attention to women’s interests, lack of food security and limited technical assistance, among other challenges. They also demand greater attention from the state and policies and programs to improve their social, economic, and environmental well-being. The visibility and valuation of the work and contributions of women and youth to production systems and conservation is also a pending task.